Environmental Assessment of Lightweight Electric Vehicles - Egede, Patricia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This monograph adresses the challenge of the environmental assessment of leightweight electric vehicles. It poses the question whether the use of lightweight materials in electric vehicles can reduce the vehicles' environmental impact and compares the environmental performance of a lightweight electric vehicle (LEV) to other types of vehicles. The topical approach focuses on methods from life cycle assessment (LCA), and the book concludes with a comprehensive concept on the environmental assessment of LEVs. The target audience primarily comprises LCA practitioners from research institutes and industry, but it may also be beneficial for graduate students specializing in the field of environmental assessment.
Lightweight Electric Vehicles -- Electric Vehicles, Lightweight Design and Environmental Impacts -- State of Research on the Environmental Assessment of Electric and Lightweight Vehicles -- Concept for the Environmental Assessment of Lightweight Electric Vehicles -- Case studies on the comparison of (lightweight) electric vehicles with conventional and reference electric vehicles -- Summary, Critical Review and Outlook.
Keywords: Automotive engineering; Transportation engineering; Traffic engineering; Sustainability; Automobile industry and trade; Energy policy; Energy and state; Automotive Engineering; Transportation Technology and Traffic Engineering; Sustainability; Automotive Industry; Energy Policy, Economics and Management